Synthesis of monodisperse water-stable surface Pb-rich CsPbCl3 nanocrystals for efficient photocatalytic CO2 reduction. Issue 22 (29th May 2020) - Zhu, Jingrun; Zhu, Yihua; Huang, Jianfei; Hou, Lu; Shen, Jianhua; Li, Chunzhong
Abstract : Monodisperse water-stable surface Pb-rich lead halide perovskite nanocrystals (NCs) were obtained by the liquid–solid interpenetration method. The maximum CO2 photoreduction rate of the obtained NCs is as high as 169.37 μmol g −1 h −1 . Abstract : Surface Pb-rich lead halide (CsPbCl3 ) perovskite nanocrystals (NCs) with high stability and monodispersity in water have been synthesized using a general and convenient liquid–solid interpenetration (LSI) method. In this process, water molecules permeate into the solid CsPbCl3 NC layers and slowly dissolve the Cs + and Cl − ions on the surface of CsPbCl3 NCs. The Cs + and Cl − ions in water inhibit the decomposition rate of CsPbCl3 NCs, inducing surface Pb-rich layers. The surface Pb-rich structure increases the photoluminescence (PL) lifetimes and improves the photocatalytic performances of lead halide perovskite NCs. Under simulated solar irradiation, the largest rate of CO2 photoreduction from surface Pb-rich Ni-doped CsPbCl3 NCs reaches up to 169.37 μmol g −1 h −1 . This study provides an effective general strategy to design stable lead halide perovskite quantum dots (QDs) for their wide applications.